Plants with less chlorophyll: A global change perspective. (13th December 2020) - Genesio, Lorenzo; Bassi, Roberto; Miglietta, Franco
Abstract: The necessary reduction of greenhouse gas (GHG) emissions may lead in the future to an increase in solar irradiance (solar brightening). Anthropogenic aerosols (and their precursors) that cause solar dimming are in fact often co‐emitted with GHGs. While the reduction of GHG emissions is expected to slow down the ongoing increase in the greenhouse effect, an increased surface irradiance due to reduced atmospheric aerosol load might occur in the most populated areas of the earth. Increased irradiance may lead to air warming, favour the occurrence of heatwaves and increase the evaporative demand of the atmosphere. This is why effective and sustainable solar radiation management strategies to reflect more light back to space should be designed, tested and implemented together with GHG emission mitigation. Here we propose that new plants (crops, orchards and forests) with low‐chlorophyll (Chl) content may provide a realistic, sustainable and relatively simple solution to increase surface reflectance of large geographical areas via changes in surface albedo. This may finally offset all or part of the expected local solar brightening. While high‐Chl content provides substantial competitive advantages to plants growing in their natural environment, new plants with low‐Chl content may be successfully used in agriculture and silviculture and be as productive as the green wildtypes (or even more). The most appropriate strategies to obtain highly productive and highly reflective plants are discussed in this paper and their mitigation potential is examined together with the challenges associated with their introduction in agriculture. Abstract : Climate change mitigation policies aimed at the reduction of greenhouse gas (GHG) emissions might cause an increase in solar irradiance in the most populated areas of the planet (solar brightening). Anthropogenic aerosols causing solar dimming are co‐emitted with GHGs. New plants with low‐chlorophyll (Chl) content may offset such brightening. Their introduction increases surface reflectance (albedo) of large geographical areas, thus reducing the shortwave radiative forcing (RFSW). Additional benefits such as reducing transpiration and/or mitigating local effects of extreme temperatures may be obtained. Genome editing aims to create those new plants targeting both appropriate optical properties and enhanced productivity.